Characteristics and clinical outcomes of Japanese patients with venous thromboembolism receiving under-dose rivaroxaban: subanalysis of J'xactly. (3rd July 2022) - Fukamachi, Daisuke; Okumura, Yasuo; Fukuda, Ikuo; Nakamura, Mashio; Yamada, Norikazu; Takayama, Morimasa; Maeda, Hideaki; Yamashita, Takeshi; Ikeda, Takanori; Mo, Makoto; Yamazaki, Tsutomu; Hirayama, Atsushi; et al.
Abstract: Objective: Rivaroxaban is commonly prescribed to prevent venous thromboembolism (VTE). Although lower than standard dosages (under-dosing) may be administered in the real-world setting, data on subsequent clinical outcomes in Japanese patients are lacking. Methods: The prospective, multicenter, observational J'xactly study enrolled patients with acute symptomatic/asymptomatic deep vein thromboses (DVT), pulmonary embolism (PE), or both, who were prescribed rivaroxaban. This subanalysis investigated patient characteristics and outcomes associated with rivaroxaban under-dosing. Results: Among 1016 evaluable patients, 667 (65.6%) received an initial standard dosage of rivaroxaban (30 mg/day) and 349 (34.4%) received an initial under-dosage (20 mg/day, n = 22; 15 mg/day, n = 282; and 10 mg/day, n = 45). Those receiving an under-dose had significantly lower body weight and slower pulse rate compared with the standard-dose group regardless of DVT or PE status. Under-dosing was common for distal DVTs, but less frequent for massive/submassive PEs. There were no differences between under-dose and standard-dose groups in the incidences of recurring symptomatic VTEs (DVT: 1.77% vs. 3.35% per patient-year, p = .138; PE: 0.84% vs. 2.84% per patient-year, p = .208) or major bleeding (DVT: 3.55% vs. 3.41% per patient-year, p = .960; PE: not observed vs. 2.83% per patient-year, p = .132). Conclusions: In the real-world setting, rivaroxaban under-dosing for patients with VTE occurred in those with lower body weight, slower pulse rate, distal DVT, or non-massive PEs. There were no statistically significant differences in the clinical outcomes for patients received under-dose of rivaroxaban at the discretion of the physicians in the clinical practice compared with those received standard dose of rivaroxaban.